Perancangan Materi Pembelajaran Uji Kadar Air dengan Metode Gravimetri Berbasis Android - Hatigoran, Geraldo; Birowo, Sigit; Fa, Liaw Bun (Institut Bisnis dan Informatika Kwik Kian Gie, 2024)
The development of information technology in this era of globalization is very rapid. Especially smartphone. The use of this smartphone can be applied to other applications, for example, a learning application for testing water content with the gravimetric method. Water content testing is one of the important chemical laboratory test methods in the food industry to determine the quality and resistance of food to damage that may occur. The gravimetric method is one of analytical chemistry in chemistry that serves to determine the quantity of a substance and component that is already known by measuring the weight of the component after going through a separation in a pure state. This research was conducted using qualitative methods. The system design of this study is described in the form of an interface design, and the Unified Modeling Language (UML). The results of this system research in the form of a Gravimetric System application that can assist the course of gravimetric testing. The design of this system is also described in the form of a program guide that will explain the functions and features available. This research resulted in an application for water content testing tools with an android-based gravimetric method that can assist in the definition of the material and the simulation of this test.